The influence of domestic dogs on the spatial and temporal distribution of tayra - Manzo, Isabele Aparecida [UNESP]; Gonçalves da Silva, Rodolpho [UNESP]; Bianchi, Rita C. [UNESP] (Wiley, 2025)
The domestic dog Canis familiaris is an exotic species known to have impacts on native fauna and it may induce spatial and temporal segregation in other species as a mechanism to reduce agonistic interactions. The tayra Eira barbara, a medium-sized, widely distributed mustelid, is one of the species that can be affected. To test this hypothesis, between 2020 and 2022, we installed camera traps in an agricultural landscape composed of a protected area, agro-livestock areas, an urban area, and several rural households. We calculated the activity patterns, their overlapping coefficients and generated models to explain the species's occupancy and verify possible interferences. We obtained 32 records of tayras and 100 of domestic dogs. In only 8 of 73 sampling points, the two species occurred concomitantly. Activity overlap was 68%; however, at the points where both species occurred, the overlap was 43%. Tayra showed to be positively associated with forest areas, and negatively with agricultural exploitation areas. Dogs predominantly occupied agricultural areas and were negatively related to forest areas. In addition to dog interference, which seems to affect tayra's use of the landscape, environmental conditions are also essential in describing the occupancy of the subordinate species. It is possible that their scansorial habit is important to avoid agonistic events.
Keywords: Canis familiaris; Eira barbara; interaction between carnivores; multispecies occupancy model; space use; temporal avoidance